FROM AL-WAHIDI TO AL-SUYUTI: THE EVOLUTION OF ASBAB AL-NUZUL THOUGHT - Zaky, KGS. Muhammad; Masruhan; Ahmad Alfian Jihadi; Zaki, KGS. Muhammad (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2025)
The study of asbab al-nuzul occupies an important position in ulum al-Quran because it serves as a bridge between the text of revelation and its historical context. Two central figures who exerted significant influence in this discipline are al-Wahidi (d. 468 AH) and al-Suyuti (d. 911 AH). This article aims to examine the evolution of asbab al-nuzul thought in the works of these two scholars by employing qualitative methods through a library-based approach, as well as historical, comparative, and philosophy-of-science frameworks to analyze the aspects of nature (ontology), sources of knowledge (epistemology), and the function of asbab al-nuzul (axiology). This study shows that, ontologically, al-Wahidi understood asbab al-nuzul as broad historical events that could have occurred long before the revelation of a verse, whereas al-Suyuti restricted them to incidents occurring simultaneously with the descent of the verse. From an epistemological perspective, al-Wahidi’s approach is more compilatory without deep scrutiny of transmission chains, while al-Suyuti applied stricter selection and validation of reports. Axiologically, al-Wahidi positioned the causes of revelation as the basis for understanding meaning and legal rulings, whereas al-Suyuti strengthened the function of asbab al-nuzul through more authentic and comprehensive narrations to support more authoritative interpretation. Thus, this study affirms that there was a significant evolution from a compilatory-descriptive stage to a methodological-critical one. The contribution of this article lies in demonstrating the relevance of ontological, epistemological, and axiological frameworks in tracing the development of Quranic exegesis, while also opening space for the actualization of asbab al-nuzul in contemporary scholarship.